Foucault, Laughter, and Gendered Normalization - Emily R. Douglas (Foucault Studies, 2015)
Thus far, little attention has been paid by Foucauldian scholars to the role of laughter in our subjectivation and normalization, nor to the possible roles of laughter practices in political resistance. Yet, there is a body of references to laughter in both Foucault’s own work and that of his contemporary commentators, subtly indicating that it might be a tool for challenging normalization through transgression. I seek to negotiate the different functions (both transgressive and disciplinary) that our laughter practices can have, proposing that laughter is a worthy site of exploration for Foucauldian feminists in particular. Examining the differential norms, requirements, and sanctions around laughter shows that we are shaped as gendered subjects through the regulation of laughter’s timing and its bodily presentation. I argue that the contemporary state of laughter practices works to uphold docile femininity, using tools such as compulsory happiness and labelling feminists as killjoys. In brief, this article interrogates the ways in which cultivating different laughter practices can function as a path for Foucauldian-feminist political resistance.